Antimicrobial activity of a novel hypervariable immunoglobulin domain-containing receptor Dscam in Cherax quadricarinatus. Issue 2 (December 2015) - Li, Dan; Yu, Ai-Qing; Li, Xue-Jie; Zhu, You-Ting; Jin, Xing-Kun; Li, Wei-Wei; Wang, Qun
Abstract: Down syndrome cell adhesion molecule (Dscam) mediates innate immunity against pathogens in arthropods. Here, a novel Dscam from red claw crayfish Cherax quadricarinatus (CqDscam) was isolated. The CqDscam protein contains one signal peptide, ten immunoglobulin domains, six fibronectin type III domains, one transmembrane domain and cytoplasmic tail. CqDscam phylogenetically clustered with other invertebrate Dscams. Variable regions of CqDscam in N-terminal halves of Ig2 and Ig3 domains, complete Ig7 domain and TM domain can be reshuffled after transcription to produce a deluge of >37, 620 potential alternative splice forms. CqDscam was detected in all tissues tested and abundantly expressed in immune system and nerve system. Upon lipopolysaccharides (LPS) and b-1, 3-glucans (Glu) challenged, the expression of CqDscam was up-regulated, while no response in expression occurred after injection with peptidoglycans (PG). Membrane-bound and secreted types of CqDscam were separated on the protein level, and were both extensively induced post LPS challenge. Membrane-bound CqDscam protein was not detected in the serum, but localized to the hemocyte surface by immuno-localization assay. In the antimicrobial assays, the recombinant LPS-induced isoform of CqDscam protein displayed bacterial binding and growth inhibitory activities, especially with Escherichia coli . These results suggested that CqDscam, as one of pattern-recognition receptors (PRRs), involved in innate immune recognition and defense mechanisms in C. quadricarinatus, possibly through alternative splicing. Highlights: A novel hypervariable Dscam gene in Cherax quadricarinatus (CqDscam) was cloned and analyzed, which may produce >37, 620 unique isoforms. CqDscam phylogenetically clustered with other crustacean Dscam proteins. CqDscam was detected in all tissues, and was inducible in hemocytes upon challenge with lipopolysaccharides. The recombinant LPS-induced CqDscam protein has ability to binding and inhibit growth of microorganisms.